Enriching adenosine by thymine-rich DNA oligomers. Issue 8 (21st March 2023) - Liu, Mingchun; Chen, Huaiqing; Huang, Yuhan; Liu, Jian; Chen, Qianfeng; Zuo, Hua; Fang, Liang; Mao, Chengde
Abstract : Proposed model for the complexes formed by poly(thymine) (poly(T)) and Ado (or adenine). Complexes formed from ado/adenine and (a) poly(T) strands, (b) a hairpin-containing poly(T) strand, and (c) a clamp-containing poly(T) strand. Abstract : Adenosine levels are important in various physiological and pathological activities, but detecting them is difficult because of interference from a complex matrix. This study designed a series of DNA oligomers rich in thymine to enrich adenosine. Their binding affinity ( K d range: 1.25–5.0 mM) to adenosine varied based on the DNA secondary structures, with a clamped hairpin structure showing the highest binding affinity. Compared to other designs, this clamped DNA hairpin underwent the least conformational change during adenosine binding. These DNAs also suppressed the precipitation of supersaturated adenine. Taken together, these results suggest that thymine-rich DNAs could be used to enrich and separate adenosine.